C–H bond activation of benzene and thiophene by photochemically generated rhenocene cation - Hiroshi Ogino; Hiromi Tobita; Kouji Endo; Kiyonari Hashidzume (International Journal of Photoenergy)
A cationic rhenocene-acetonitrile adduct [Cp2Re(NCMe)](BF4)(1) reacted with an excess of benzene, thiophene, 2-methylthiophene, and pyrrole under UV irradiation to afford the C–H bond activation products [Cp2Re(H)R]BF4 (R = phenyl, 2-thienyl, 2-(5-methylthienyl), 2-pyrrolyl) in high yields. In cases of thiophene derivatives and pyrrole, α-C–H bonds are selectively activated. A plausible mechanism involves the photodissociation of acetonitrile from 1 to generate a coordinatively unsaturated rhenocene cation [Cp2Re]+. When 2,5-dimethylthiophene and dibenzothiophene, having no α-C–H bonds, were used as substrates, products of the activation of other C–H bonds were formed first, but they isomerized to thermodynamically more stable η11-S-coordinated complexes in refluxing acetone. On the other hand, irradiation of the η1-S-coordinated complexes reproduced the original C–H bond activation products. Because of the cationic character, [Cp2Re(H)R]BF4 were readily deprotonated by triethylamine to give neutral rhenocene derivatives Cp2ReR. When R is thienyl or 2-(5-methylthienyl), treatment of Cp2ReR with HBF4⋅Et2O and MeI resulted in protonation and methylation to give [Cp2Re(H)R]BF4 (R = and [Cp2Re(Me)R]I. Thermolysis of [Cp2Re(Me)R]I in the presence of PPh3 unexpectedly resulted in migration of R to the Cp ring to give [(2 thienyl C5H4)CpRe(PPh3)]I.